Pengembangan Bahan Ajar dan Pembelajaran Program Keagamaan pada MA Aceh Besar - T M Hasan (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
This study is intended to gain more information on the development of instruction materials in teaching and learning process at Islamic Senior High Schools in Aceh Besar, Aceh, Indonesia. This study used qualitative approach to reveal hidden things behind the realities. To collect data, I employed several techniques including interviews, observations, and documentations. This study found that the development of teaching materials had been done by teachers of Islamic Senior High schools in Aceh Besar. There were several forms of development including enriching teaching materials using various references; writing modules; making summary of learning materials and; combining different teaching strategies according to the learning materials and objectives.